CSPM for Healthcare: Securing Electronic Health Records (EHR) and Ensuring HIPAA Compliance - Nikhil Tej Gandhi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cloud Security Posture Management (CSPM) has emerged as a critical solution for healthcare organizations navigating the complexities of digital transformation and cloud adoption. This comprehensive article examines how CSPM tools help healthcare providers secure Electronic Health Records (EHR) while maintaining HIPAA compliance in cloud environments. The article explores key challenges in maintaining data privacy and security requirements, evaluates the role of CSPM in automated security assessment and compliance monitoring, and presents real-world case studies demonstrating successful implementations. Additionally, it investigates future directions in CSPM development, including artificial intelligence integration and enhanced data protection features, providing insights into the evolving landscape of healthcare security management.